Recruitment of consultant psychiatrists from low- and middle-income countries - Ndetei, David (Int Psychiatry, 2004)
The UK’s 2-year International Fellowship Programme for consultant doctors has inadvertently highlighted the long-standing issues of the costs and benefits of such recruitment for the countries of origin, and of whether it is ethical for rich countries to recruit health personnel not only from other rich countries but also from low- and middle-income countries. The ‘brain drain’ from poor to rich countries has been recognised for decades; it occurs in the health sector as well as other sectors, such as education, science and engineering. It has had serious ramifications for the health service infrastructure in low-income countries, where poverty, morbidity, disability and mortality are increasing rather than decreasing, and it is a matter of serious concern for both the World Health Organization and the International Monetary Fund (Carrington & Detragiache, 1998; Lee, 2003).